Production of Shadow Puppet Performances in Building Artistic Entrepreneurship - Juju Masunah; Putri Lilis Dyani; Vanessa Gaffar; Maya Sari (Journal of Sustainable Tourism and Entrepreneurship, 2022)
Purpose: This research describes the efforts to promote entrepreneurial motivation through shadow puppet performances. Research Methodology: This research used a project-based approach, and the activities are initiated by: 1) diagnosing the problems of performing arts entrepreneurship, 2) creating art incubation designs, 3) implementing activity plans, and 4) evaluating activities through performances. The participants were students with educational backgrounds in dance, music, and fine arts at Universitas Pendidikan Indonesia, as well as partners in the Indigo Moon Theater, a community-based in London. Results: A production of shadow puppet performance art with a Jungle Book story can foster students’ entrepreneurial motivation, shown through paid performances and business planning sales of show packages, merchandise, and a shadow puppet workshop model for children and families. Limitations: This research cannot assist the participants in managerial work to continue their business. Contributions: This research contributes to developing art entrepreneurship in the performing arts field as part of Indonesia’s creative industry sub-sector.